2004
DOI: 10.1055/s-2004-821138
|View full text |Cite
|
Sign up to set email alerts
|

Fournier's Gangrene in Neonates and Infants

Abstract: Fournier's gangrene in neonates and infants in our environment is largely preventable. Early debridement and appropriate antibiotics give good results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 5 publications
0
22
1
5
Order By: Relevance
“…In contrast to that, more recent work has shown that the perineal gangrene as well as all other manifestations of necrotizing fasciitis is not limited to young individuals, nor is it limited to men [5,6]. Reports have been published about the appearance of the infection in elderly men, women, children an even in newborns [4][5][6][7]. However, predisposing factors as diabetes mellitus, alcoholism, immunosuppressant therapy, liver and renal diseases are frequent, although not obligatory [8][9][10].…”
Section: Epidemiological Clinical and Diagnostic Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to that, more recent work has shown that the perineal gangrene as well as all other manifestations of necrotizing fasciitis is not limited to young individuals, nor is it limited to men [5,6]. Reports have been published about the appearance of the infection in elderly men, women, children an even in newborns [4][5][6][7]. However, predisposing factors as diabetes mellitus, alcoholism, immunosuppressant therapy, liver and renal diseases are frequent, although not obligatory [8][9][10].…”
Section: Epidemiological Clinical and Diagnostic Featuresmentioning
confidence: 99%
“…However, predisposing factors as diabetes mellitus, alcoholism, immunosuppressant therapy, liver and renal diseases are frequent, although not obligatory [8][9][10]. There is a higher prevalence of the disease in poorly developed countries [4,6,7,11]. While Fournier himself thought the disease to be idiopathic, nowadays, in most cases, the origin of the infection is known or may be evaluated [5].…”
Section: Epidemiological Clinical and Diagnostic Featuresmentioning
confidence: 99%
“…Pediatric involvement is rare. The use of nonsteroidal antiinflamatory drugs (NSAID) have been found to be associated with Fournier's gangrene in children, besides other causes [1][2][3][4][5][6]. In the present case Fournier's gangrene was associated with neglected prolonged diarrhea, perianal excoriation resulting from diarrhea, and poor hygiene which has not been reported in literature so far.…”
Section: Introductionmentioning
confidence: 57%
“…The necrotizing fasciitis commonly originates from an infection of the anorectum, urogenital tract or the skin of the genitals [3]. The predisposing factors linked to Fournier's gangrene in children, which are mentioned in literature are NSAIDs use, post varicella infection, diaper rash, prematurity, circumcision, strangulated hernia, testicular torsion, trauma and insect bite [1,[4][5][6]. The treatment of Fournier's gangrene in children is equivocal.…”
Section: Discussionmentioning
confidence: 99%
“…In the pediatric literature there is description of healing with limited excision of scrotal afection. (Ameh et al, 2004) …”
Section: Age and Sexmentioning
confidence: 99%